1976
DOI: 10.1152/ajplegacy.1976.231.2.313
|View full text |Cite
|
Sign up to set email alerts
|

An examination of transcapillary water flux in renal inner medulla

Abstract: We recently demonstrated that net fluid uptake occurs in the capillary system of the inner medulla. To define the site of fluid uptake, the concentration of protein was determined in plasma from descending vasa recta at the base and tip of the exposed papilla in Munich-Wister rats. The vasa recta plasma-to-arterial plasma protein concentration ratio (VR/P) was 1.43 +/- 0.09 at the base and 1.66 +/- 0.09 at the tip. These results, which indicate fluid loss from the descending vasa recta, are difficult to explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 4 publications
6
21
0
Order By: Relevance
“…The rats remained nondiuretic throughout the study as indicated by the mean ratios for urine-to-systemic plasma osmolality and urine-to-systemic plasma inulin. (21) and, in a later study (22), of VR at the papillary tip were slightly lower than 7 g/100 ml. In correcting the present data for plasma water we used the highest mean value.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The rats remained nondiuretic throughout the study as indicated by the mean ratios for urine-to-systemic plasma osmolality and urine-to-systemic plasma inulin. (21) and, in a later study (22), of VR at the papillary tip were slightly lower than 7 g/100 ml. In correcting the present data for plasma water we used the highest mean value.…”
Section: Resultsmentioning
confidence: 62%
“…If the protein concentration in medullary interstitial fluid is less than that in VR plasma (and there are reasonable grounds for assuming it is [22]), then the cation concentration in the interstitium is less than that in VR plasma water and the difference in sodium concentration between fluid in Henle's thin limb and the interstitium is greater than that calculated by neglecting the GibbsDonnan equilibrium. Therefore use of VR plasma sodium concentration uncorrected for the GibbsDonnan distribution will underestimate the actual loop fluid-vasa recta plasma (LH-VR) sodium gradient.…”
Section: Resultsmentioning
confidence: 99%
“…These cells express the AQP1 water channel that is responsible for small-solute-driven efflux of water to the medullary interstitium (118,137). Thus, in opposition to the classic view of purely diffusive countercurrent exchange, water abstraction is an important mode of DVR equilibration.…”
Section: Discussionmentioning
confidence: 99%
“…That transport proceeds in a direction opposite to inwardly directed Starling forces (hydraulic and oncotic pressure), thus implicating transmural small-solute osmotic gradients as the responsible driving force (98,118,137,138). For NaCl and urea gradients generated by the lag in equilibration between DVR plasma and medullary interstitium to induce water efflux, the water must traverse a pathway of sufficiently small pore size for these solutes to be osmotically active.…”
Section: Transport Of Solutes and Water Across Vasa Rectamentioning
confidence: 99%
“…With respect to the transport of water, classical Starling forces (hydraulic and oncotic pressure) can drive water flux across outer medullary descending vasa recta (OMDVR) via a shared pathway where small hydrophilic solutes are also transported (6). In vivo, however, it has been shown that water efflux occurs across the descending vasa recta (DVR) wall at some location between the corticomedullary junction and papillary tip, despite the existence of Starling forces that favor volume influx (7). It was proposed that water efflux involves a water-only pathway in which NaCl and urea gradients are able to drive water movement, and that the water-only pathway might comprise aquaporin-1 (AQP1) water channels (8,9).…”
Section: Introductionmentioning
confidence: 99%